Penerapan Model Number Head Together (NHT) untuk Meningkatkan Keterampilan Menulis Narasi Ekspositoris di Kelas Tinggi - Muhammad Pujo (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The objectives of this research are to describe NHT model implementation and also to describe the result which shows improvements in expository narrative writing skills. This research is based on Classroom Action Research. Data are collected through tests, documentations, and observation sheets for teachers and students. It uses quantitative descriptive analysis technique. NHT model implementation affected well showing improvements in every conducted action. The result shows average pre-cycles score of 51,81 with 26% classical completeness. After actions conducted using NHT model, cycle 1 shows average score of 63,1 with 61% classical completeness and cycle 2 shows average score of 75 with 84% classical completeness. The result of expository narrative writing skill are calculated using gain score, which showing a score of 0,48 with medium category.